Anaemia in HIV positive mothers on antiretroviral therapy for prevention of mother-to-child transmission HIV in a tertiary health institution in North Central Nigeria - Adewole, Nathaniel D.; Okechukwu, Adaora A.; Offiong, Richard A.; Adebayo, Francis O.; Isah, Dennis A.; Akitoye, Olumide A. (International Journal of Research in Medical Sciences, 2021)
Background: Anaemia in pregnancy and HIV infection are two common public health issues in sub-Saharan African with Nigeria bearing the greatest burden. The duo occurring together poses a higher risk of morbidity and mortality for both the foetus and the mother. We therefore conducted this study to determine the burden of anaemia and other haematological abnormalities among HIV positive pregnant mothers on antiretroviral therapy who attended antenatal clinical services in our health institution. Methods: A 10-year retrospective review from January 2010 to December 2019 of medical records of HIV positive mothers on highly anti-retroviral therapy in attendance for antenatal clinical services in our health institution was carried out for the above objectives. Information extracted were, age, HIV status, gestational age at delivery, type of antiretroviral drugs used, duration of use, haemoglobin level, platelet, and complete blood count at booking of the positive mothers. Results: Of a total of 330 HIV positive mothers seen during the review period, 82.7% were from rural communities, 88.8% were from middle socio-economic class, 80.0% were Christians, and 80.3% started their highly active antiretroviral therapy before their index pregnancy. Most, 51.5% and 42.7% were on zidovudine, lamivudine and nevirapine, and tenofovir with lamivudine and lopinavir boasted ritonavir combinations, while 94.2% were on 1st line antiretroviral medication. Their mean age, gestational age at delivery, and parity were 31.11±4.7 years, 38.57±3.1 weeks, and 2.0±1.6 respectively. The prevalence of anaemia, thrombocytopenia and leucopoenia were 36.1%, 4.8%, and 6.7% respectively while their mean CD4 cell count and viral loads at the point of booking were 543.63±283.7 cells/μl, and 2953.02±1619.9 copies/ml. The two maternal variables that showed significant relationship with haemoglobin concentration of <10 gm/dl was mother’s level of education x2=6.29, p=0.043, and her socio=economic class, x2=10.162, p=0.006. Conclusions: There is high burden of anaemia among HIV positive mothers on antiretroviral therapy in our environment. The prevalence of thrombocytopenia and leucopoenia was much lower. The burden of maternal anaemia was associated with maternal level of education and her socio-economic class.